Celiac Disease in Women With Infertility: A Meta-Analysis. Issue 1 (January 2016) - Singh, Prashant; Arora, Shubhangi; Lal, Suman; Strand, Tor A.; Makharia, Govind K.
Abstract : Background: Celiac disease (CeD) is a systemic disease with manifestations not limited to small intestine. The data on association between CeD and infertility is contradictory. There are no recommendations for the screening of female patients with infertility for CeD. Aim: We conducted a meta-analysis to find out whether women with infertility are at higher risk of CeD. Methods: Literature search was performed using the MeSH keywords "CeD, " "gluten, " and "infertility." Diagnosis of CeD was based on positive serology and biopsies showing villous atrophy. Data were extracted about CeD patients in 3 groups—women with infertility (including unexplained infertility), unexplained infertility, and controls. Pooled odds ratio (OR) and prevalence, with 95% confidence intervals (CI), were calculated. Results: Of 105 relevant studies, 5 studies were included for calculation of pooled OR. Four additional studies, where data on controls were not available, were also considered for calculation of pooled prevalence of CeD. Women with infertility had 3.5 times higher odds of having CeD in comparison with control population (OR=3.5; 95% CI, 1.3-9; P <0.01). Similarly, women with "unexplained infertility" had 6 times higher odds of having CeD than controls (OR=6; 95% CI, 2.4-14.6). Of 884 women with infertility, 20 had CeD indicating a pooled prevalence of 2.3% (95% CI, 1.4-3.5). Of 623 women with "unexplained infertility, " 20 had CeD. The pooled prevalence of CeD in women with unexplained infertility was 3.2 (95% CI, 2-4.9). Conclusions: CeD is more prevalent in women with "all-cause" infertility and "unexplained" infertility than that in general population.